PERBANDINGAN CIRCUIT TRAINING DAN INTERVAL TRAINING TERHADAP VO2 MAX DENGAN INDEKS MASSA TUBUH PEMAIN BOLA VOLI - Sumintarsih, Sumintarsih; Saptono , Tri; Mustofa, Hanafi; Indriharta, Lilik (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2022)
This study used an experimental method with a 2x2 factorial design. The population in this study was players of the BSA Volleyball club (Balangan Student Assosiasion), Sendangsari, Minggir, Sleman Yogyakarta, the size of the sample was 24 athletes. This research data analysis technique uses ANAVA. Test the prerequisites of data analysis using the normality test (Lilliefors test with α = 0.05) and the variance homogeneity test (Bartlet test with α = 0.05). The results of the study are as follows: 1) There is a difference in the influence between low BMI with an average of 3.844166667 and high BMI with an average of 2.5283333333 on increasing VO2 max ability with an average selisish of 1.315833334. 2) There is a difference in the influence between the circuit training method with an average of 2.716666667 and the training interval with an average of 3.655833333, on the increase in VO2 Max capability with an average difference of 0.939166666. 3) There is a difference in the effect between low IMT circuit training with an average of 3.001666667 and low BMI training intervals with an average of 4.686666667 on the increase in VO2 Max capability with an average difference of 1.685. 4) there is a difference in the effect between high BMI circuit training with an average of 2.431666667 and high BMI training intervals with an average of 2.626 on the increase in VO2 max the average difference of 0.193333333. 5) Interaction between BMI and exercise method 1.45530676.